Tanzania Africa Research in Sustainable Intensification for the Next Generation (Africa RISING) Follow-up Survey - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
Tanzania Africa RISING follow-up evaluation survey was implemented in 2022. The survey data were collected from the same households that were interviewed as part of the Tanzania baseline evaluation survey. Please refer to "A User Guide to Tanzania Africa Research in Sustainable Intensification for the Next Generation (Africa RISING) Baseline Evaluation Survey Data" data paper for details about survey coverage and design. The Tanzania follow-up survey was implemented using structured questionnaires that were highly comparable with the questionnaires used in the Tanzania baseline evaluation survey.